Remaking the American university : market-smart and mission-centered - Zemsky, Robert, 1940- (Rutgers University Press, 2005)
At one time, universities educated new generations and were a source of social change. Today colleges and universities are less places of public purpose, than agencies of personal advantage. Remaking the American University provides a penetrating analysis of the ways market forces have shaped and distorted the behaviors, purposes, and ultimately the missions of universities and colleges over the past half-century. The authors describe how a competitive preoccupation with rankings and markets published by the media spawned an admissions arms race that drains institutional resources and.